Linking hazard intensity to impact severity: mini review of vulnerability models for volcanic impact and risk assessment - Hayes, Josh L.; Fitzgerald, Rebecca H.; Wilson, Thomas M.; Weir, Alana; Williams, James; Leonard, Graham (Frontiers in Earth Science, 2024)
Volcanic eruptions can cause significant impacts on communities and infrastructure. There is an increasing need for effective risk assessments to inform decision-making and minimise the impact of volcanic hazards. Vulnerability models play a crucial role in these assessments, connecting the intensity of the hazard with the elements that are exposed to it, allowing for the calculation of potential impact or risk. There has been a large increase in the number of vulnerability models being developed for volcanic risk applications, and there is now a need to identify knowledge gaps for the field to take a strategic approach moving forward. This review aims to provide a high-level overview of the current state of volcanic vulnerability modelling and identify areas for future development. We evaluated 594 vulnerability models covering a range of elements and sectors, including buildings, critical infrastructure, transportation networks, agriculture, and human vulnerability. We reviewed the types of hazard intensity metrics and impact/risk metrics used in the models, modelling methodologies, underpinning data requirements, and uncertainty characterisation. A global clearinghouse for volcanic vulnerability models would be advantageous for the volcanic risk community to identify appropriate vulnerability models quickly and efficiently for their needs. As a first step towards such a clearinghouse, we have uploaded this volcano vulnerability model compilation to a repository and encourage additions/suggestions from the community on its future development. The results of this study will contribute to the advancement of the field and provide valuable insights for future research and development in volcanic risk assessment.